Socially Inclusive heritage conservation land-use management in small towns: a case study in the Greater Oudtshoorn Municipality - Adendorff, Rudi (Stellenbosch : Stellenbosch University, 2025)
Thesis (MA)--Stellenbosch University, 2024.